A comparative study of 15-isoprostane f2t in blood of extra hepatic cholestasis children and healthy children. - MARYAM Q.AHMAD, (International Journal of Pharma and Bio Sciences, 2018)
Cholestasis is impairment of bile the digestive fluid secretion caused by dysfunction of hepatocytes or obstruction of bile flow through intra-or extra hepatic bile ducts. Cholestasis always indicates a pathological process that can result in chronic liver dysfunction, the necessity of liver transplantation and even death .Cholestasis canoccurat any age. Oxidative stress occurs as a consequence of imbalance between the formation of oxygen free radicals and in activation of these species by antioxidant defense system .15-isoprostane F2t has been proposed as good indicator of oxidative stress, 15-isoprostane F2t have been found in the blood of patients with cholestasis. The purpose of this study is to investigate Comparison of oxidative stress between two group by determine 15-is prostate F2t. In the cholestasis patients, a significant increase was found in mean levels of 15-isoprostane F2t compared to control children.15 isoprostane F2 t In the cholestasis patients was 47.03±26.193 and in control children was 0.73±1.17, Oxidative stress may potentially be used as diagnostic markers of disease progression.